An experimental investigation to assess the influence of container loading configuration on the effects of a crosswind on a container freight train. Issue 145 (October 2015) - Soper, David; Baker, Chris; Sterling, Mark
Abstract: Relative crosswinds when coupled with transient aerodynamic effects associated with freight trains can have large velocity magnitudes, potentially affecting the stability of not only the train but also containers loaded onto the train. This paper describes a series of moving model crosswind experiments conducted at the University of Birmingham's TRAIN rig facility using a Class 66 hauled container freight train fitted with an on-board surface pressure monitoring system. In the paper the term 'freight train' refers to a series of flatbed wagons loaded with ISO standard shipping containers hauled by a Class 66 locomotive. By altering the container loading efficiency it was possible to develop an understanding of influencing factors on forces subjected to a loaded container. Surface pressure coefficient data has been recorded at a yaw angle of 30°; and were compared with data corresponding to a typical passenger train. In general, similar magnitudes of pressure coefficients have been observed. However, areas associated with large flow separation exhibited greater magnitudes than previously observed. The pressure coefficient magnitudes measured on the container surface exhibited clear dependence on container loading configuration. A series of pressure gradients were observed for different container faces, relating to the crosswind flow over the container and a series of vortices formed at unshielded container edges. It was possible to calculate the overall mean aerodynamic load coefficients as a discrete integral of forces acting on each pressure tap area. Larger magnitudes for aerodynamic load coefficients were observed as container loading efficiency was reduced and the space size in front of the measuring container increased. Overall the results from this paper offer for the first time a definitive study on the influence of container loading configuration on the characteristics of aerodynamic loads subjected to a container freight train travelling through a crosswind.